Corelink: A Web-Based Broadband Identity and Management System - Jeffry J Cabalog; Joanna Keren A Abogaa; Vapor Marian P Sending; Jeremy M Aguilar; Mary Jean T Cabalog; Mark Rey Z Embodo; Warnner Daminar Amin (MDP Student Conference, 2026)
Small Internet Service Providers often struggle with manual processes, delayed updates, and limited network automation. To address these challenges, this study developed Corelink, a web-based broadband identity and management system that improves subscriber management, network monitoring, and ISP operations through automated billing, real-time monitoring, bandwidth control, and organized workflows. Developed using the Iterative Incremental Model, the system was evaluated through a mixed-method approach using ISO/IEC 9126 criteria and user interviews. Results showed excellent performance, with administrators and users giving high ratings across all quality attributes, confirming that Corelink enhances efficiency, accuracy, and security. The study supports SDG 8 and SDG 9 by promoting efficient digital operations and strengthening broadband infrastructure.